2013
DOI: 10.4049/jimmunol.1200822
|View full text |Cite
|
Sign up to set email alerts
|

The Downregulation of microRNA let-7a Contributes to the Excessive Expression of Type I Collagen in Systemic and Localized Scleroderma

Abstract: Systemic and localized scleroderma (SSc and LSc) is characterized by excessive deposition of collagen and tissue fibrosis in the skin. Although they have fundamental common characteristics including autoimmunity, little is known about the exact mechanism that mediates the excessive collagen expression in these disorders. In the current study, we tried to evaluate the possibility that microRNAs (miRNAs) play some roles in the pathogenesis of fibrosis seen in these diseases. miRNA expression patterns were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 54 publications
6
111
0
Order By: Relevance
“…Down regulation of let7a contributes to the accumulation of type I collagen in fibroblasts in the context of SSc, and the intermittent overexpression of let7a in the skin by intraperitoneal miRNA injection improved skin fibrosis induced by bleomycin in mice. 80 In fibroblasts from healthy donors, miR196a func tions to inhibit the production of type I collagen 72 and its expression is under the control of the discoidin domain receptor 2 (DDR2). 81 However, in fibroblasts from patients with SSc, the increased production of TGFβ directly inhibits the expression of both miR196a and DDR2, thereby impairing the miR196amediated nega tive feedback that controls type I collagen production and tissue fibrosis.…”
Section: Mir-21mentioning
confidence: 99%
“…Down regulation of let7a contributes to the accumulation of type I collagen in fibroblasts in the context of SSc, and the intermittent overexpression of let7a in the skin by intraperitoneal miRNA injection improved skin fibrosis induced by bleomycin in mice. 80 In fibroblasts from healthy donors, miR196a func tions to inhibit the production of type I collagen 72 and its expression is under the control of the discoidin domain receptor 2 (DDR2). 81 However, in fibroblasts from patients with SSc, the increased production of TGFβ directly inhibits the expression of both miR196a and DDR2, thereby impairing the miR196amediated nega tive feedback that controls type I collagen production and tissue fibrosis.…”
Section: Mir-21mentioning
confidence: 99%
“…Several "omics" studies, using approaches such as genomics (Katsuma et al, 2001;Zuo et al, 2002;Kaminski, 2003) and proteomics (Kypreou et al, 2008;Kim et al, 2010), have been performed so far using BLM animal models. Furthermore, some studies that comprehensively analyzed micro RNA (miRNA) regulatory networks in pulmonary fibrosis have recently gained much attention (Liu et al, 2010;Xie et al, 2011;Xiao et al, 2012;Honeyman et al, 2013;Makino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increased evidence has shown that serum miRNA levels can be biomarkers for various human diseases. Previously, for example, we demonstrated that serum let-7a levels were significantly decreased in SSc patients than in control subjects, inversely correlating with the severity of skin sclerosis (5). On the other hand, we also measured serum levels of miR-29a in SSc patients, but found that there was no significant difference in the serum miR29a levels between control subjects and SSc patients (6).…”
Section: Introductionmentioning
confidence: 65%